(untitled) (Research, Society and Development, 2021)
Pesticides are substances often described as carcinogenic initiators for some neoplasms, such as lympho-hematopoietic and breast cancer. As for cancer of the digestive system, this relationship is still poorly explored and requires more evidence. A systematic review with meta-analysis was conducted on the association between pesticides and cancer of the digestive system in the PUBMED database. Of the 567 papers found, 32 were approved for qualitative analysis and seven for meta-analysis. Hexachlorobenzene and DDT were significantly associated with colorectal cancer (MD: 15.92; CI: 6.45; 25.40) in the analysis of continuous data and showed a borderline association in the analysis of binary data (OR: 1.17; CI: 0.93; 1.47). The cyclodienes family showed similar results in both analyzes. Polychlorinated biphenyls with low dosages were also associated with colorectal cancer (MD: 38.95; CI: 12.78; 65.11). Organophosphates (OR: 0.54; 95% CI: 0.29; 0.98), carbamates (OR: 0.96; CI: 0.77; 1.21) and triazines (OR: 0.91; 95% CI: 0.74; 1.13) showed inconclusive results. This review presents positive evidence for the association of pesticides with colorectal cancer. However, more evidence is required to determine the role of pesticides in the development of other cancers of the digestive system.